Critical phenomena in the spreading of opinion consensus and disagreement - Chacoma, Andrés Alberto; Zanette, Damian Horacio (Papers in Physics, 2014)
Fil: Chacoma, Andrés Alberto. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina